Coexpression of Elo-like enzyme and [Delta]5, [Delta]4-desaturases derived from Thraustochytrium aureum ATCC 34304 and the production of DHA and DPA in Pichia pastoris - Kang, Dong-hoon; Anbu, Periasamy; Kim, Won-ho; Hur, Byung-ki (Biotechnology and bioprocess engineering, 2008)
Thraustochytrium aureum ATCC 34304 produces a high level of polyunsaturated fatty acids (PUFAs), which are typically synthesized by strings of reactions catalyzed by desaturase and elongase enzymes. In this study, the genes related to the biosynthesis of PUFAs were investigated and targeted to enable optimization of the production of PUFAs. To the best of our knowledge, this is first study to evaluate the co-expression of genes TaElo, Tad5, and Tad4genes derived from T. aureum. We found that C22 PUFAs such as docosapentaenoic acid (DPA, C22:5n-6) and docosahexaenoic acid (DHA, 22:6n-3) were synthesized from γ-linolenic acid (GLA, C18:3n-6) and stearidonic acid (SDA, C18:4n-3), respectively, as exogenous substrates via a series of reactions catalyzed by an Elo-like enzyme and Δ5, Δ4-desaturase enzymes. In addition, the results of this study revealed that the TaElo gene could synthesize the Δ6-and Δ5-elongation products. Taken together, these results confirmed that the Elo-like enzyme was involved in multiple reactions leading to the production of PUFAs and that the TaElo, Tad5, and Tad4 genes were capable of functioning together to produce DPA and DHA using GLA and SDA. [PUBLICATION ABSTRACT]